Kualitas Papan Partikel dari Limbah Batang Kelapa Sawit dan Mahoni pada Variasi Kadar Perekat Phenol Formaldehida - Shanty Sianturi; Rudi Hartono; Tito Sucipto (Peronema Forestry Science Journal, 2015)
The combination of oil palm trunk waste and mahogany’s can increase the quality of particle board. The purpose of these study were to evaluated the effect of variations of phenol formaldehyde adhesive content and to determine the most valuable adhesives content towards the quality of particle board made from waste of oil palm trunk and mahogany’s. The treatment variation were variations of PF adhesives content  were 8%, 10%, 12%, 14%, and 16%. Particle board made with size 25 cm x 25 cm x 1 cm with target density of 0,7 gr/cm3, pressure in 30 kg/cm2, and temperature in 170°C in 10 minutes. The experimental result were compared with SNI 03-2105-2006. The statistical analysis used a single completely random experimental with 3 replication. The result showed that density value was 0.49-0.56 g/mc3, moisture content was 3.52-4.25%, water absorption in immersion for 2 hours was 67.35-117.33%, and 24 hours was 75.74-132.22%, thickness swelling on immersion for 2 hours was 8.61-33.79%, and 24 hours was 10.91-35.37%, IB values was 0.44-1.36 kg/cm2, MOE values was 7090-15529 kg/cm2, and MOR values was 75.17-169.82 kg/cm2. Variations of PF adhesive give the effect of physical and mechanical properties significantly except moisture content. The physical properties in this experiment were density, moisture content, thickness swelling on immersion for 2 hours with adhesives content were 14% and 16%, also for 24 hours with adhesive content was 16%, had been fulfilling the standard. All of IB and MOE value didn’t fulfill the standard, but the value of MOR only  in 8% adhesive content didn’t fulfill the standard. The best treatment was PF adhesive content 14%.Keywords:       oil palm trunk waste, mahogany’s, phenol formaldehyde, physical and mechanical properties, particle board.